HUBUNGAN KECERDASAN EMOSIONAL DAN PENYESUAIAN DIRI TERHADAP INDEKS PRESTASI MAHASISWA TAHUN PERTAMA - Naomi Regina Simanjuntak, Ester; RVO Situmeang, Ivonne; Julianto, Endy (Jurnal Kedokteran Methodist, 2021)
Background: Emotional intelligence in self can provide the ability to motivate to survive frustration, control excessive pleasure impulses, regulate mood and keep stress from hindering the ability to think, empathize, and pray. Emotional intelligence enables students to know themselves, control themselves, motivate themselves, empathize with the surrounding environment, and have social skills that will foster awareness for learning, thereby increasing learning achievement. If students have high emotional intelligence, it will increase learning achievement. Adjustment includes mental and behavioral responses which are individual efforts to successfully overcome the needs, tensions, conflicts and frustrations experienced within themselves, so that a level of harmony can be realized between internal demands and what is expected by their environment. Students’ adaptability can affect student academic achievement. Self-adjustment can increase the positive effect on student achievement. It is hoped that a good learning adjustment in tertiary institutions will increase the learning outcomes of first-year students. If students have high self-adjustment, it will improve learning achievement. Methods: This study is a study using the literature study method or literature review. Data obtained from secondary data using documentation techniques. Data documentation is carried out based on journals related to research variables. Conclusion: There is a relationship between emotional intelligence and self-adjustment to the first year student achievement index.